Research in medical informatics - Abdul-Kareem, S.; Baba, S.; Wahid, M.I.A. (2000)
Medical informatics is concerned with the application of computers in the medical and biological sciences and has been considered a field of research in its own right for more than twenty years. In Malaysia, however, there are very few published efforts in this area. To keep up with research activities carried out worldwide and to create expertise that will be in great demand once the Malaysian Multimedia Super Corridor (MSC) Telemedicine Flagship project is implemented, it is time that Malaysians involved themselves in medical informatics research activities. For this reason, we are proposing a project that will involve the application of an artificial neural network in the domain of cancer. As a prelude to our own research, we review current research in medical informatics. This paper subsequently proposes the use of an artificial neural networks as an alternative tool for investigating cancer survival.